the The Relationship Between Clean and Healthy Living Behaviours and the Incidence of Diarrhoea Among Children in the River Basin Area of Rantau Kujang Village, South Barito Regency: HUBUNGAN PERILAKU POLA HIDUP BERSIH DAN SEHAT DENGAN KEJADIAN DIARE PADA ANAK DI DAERAH ALIRAN SUNGAI (DAS) DESA RANTAU KUJANG KABUPATEN BARITO SELATAN - Zairullah, faizal (Barigas: Medical and Health Science Journal, 2026)
The risk of diarrhea increases when clean and healthy living behavior (PHBS) is not optimally practiced, especially regarding the use of clean water, handwashing habits, and the utilization of sanitary latrines. Rantau Kujang Village is a river basin area with a relatively high incidence of childhood diarrhea, thereby necessitating a deeper investigation into the behavioral factors contributing to this condition. This study aimed to analyze the association between clean and healthy living behavior and the incidence of diarrhea among children living in the River Basin Area (DAS) of Rantau Kujang Village, South Barito Regency. Methods: This study employed an analytic observational design with a case–control approach. The sample consisted of 200 respondents, namely mothers who had children aged 5–12 years and met the inclusion criteria. The sampling technique used was purposive sampling. Data on Clean and Healthy Living Behavior (PHBS) were collected using a questionnaire that had been tested for validity and reliability, while data on the incidence of diarrhea were obtained based on a history of diagnosis by health professionals. Data analysis was conducted using univariate and bivariate analyses with Fisher’s Exact Test. The distribution of respondents based on the incidence of diarrhea in children showed that 100 respondents (50%) were in the group of children diagnosed with diarrhea and 100 respondents (50%) were in the group of children not diagnosed with diarrhea. In addition, the distribution of respondents based on Clean and Healthy Living Behavior (PHBS) also demonstrated a balanced proportion, with 100 respondents (50%) in the good category and 100 respondents (50%) in the poor category. The results of Fisher’s Exact Test yielded a p-value of 0.000 (< 0.05), indicating a statistically significant association between clean and healthy living behavior and the incidence of diarrhea in children in the Watershed Area (DAS) of Rantau Kujang Village, South Barito Regency. There is a significant relationship between clean and healthy living behavior and the incidence of diarrhea among children in the river basin area of Rantau Kujang Village. Keywords: Clean and Healthy Living Behavior, Childhood Diarrhea